Sorption and diffusion of dense carbon dioxide in a biocompatible polymer - Duarte, Ana Rita C. (2006)
Mass sorption and diffusion coefficients in one acrylate biocompatible copolymer contacted with supercritical (sc) carbon dioxide are reported. Equilibrium solubility of dense carbon dioxide in poly(methylmethacrylate-co-ethylhexylacrylate-co-ethyleneglycoldimethacrylate) (P(MMA-EHA-EGDMA)) was studied by a gravimetric method in a temperature range from 308 to 323 K and a pressure range from 10.0 to 20.0 MPa. The cross-linked copolymer presented Fickian behavior and Fick's diffusion model was applied to determine the amount of carbon dioxide present and the diffusion coefficients. Diffusion coefficients for the sorption under supercritical conditions and desorption at ambient conditions were determined and compared. Samples of P(MMA-EHA-EGDMA) with different thickness were used for comparison of the maximum sorption degree. Polymerization conditions were also varied in order to evaluate the influence of the molecular weight of the copolymer in the CO2 sorption process. To investigate the possibility of impregnating this acrylate copolymer with an anti-inflammatory drug, a preliminary experiment was performed.